2007
DOI: 10.1016/j.freeradbiomed.2007.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants preserve macrophage phagocytosis of Pseudomonas aeruginosa during hyperoxia

Abstract: Pseudomonas. aeruginosa (PA) is a leading cause of nosocomial pneumonia in patients receiving mechanical ventilation with hyperoxia. Exposure to supraphysiological concentrations of reactive oxygen species during hyperoxia may result in macrophage damage that reduces their ability to phagocytose PA. We tested this hypothesis in cultured macrophage-like RAW 264.7 cells and alveolar macrophages from mice exposed to hyperoxia. Exposure to hyperoxia induced a similarly impaired phagocytosis of both the mucoid and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(100 citation statements)
references
References 62 publications
9
91
0
Order By: Relevance
“…39 A more recent study found that hyperoxia reduces macrophage phagocytosis and that exogenous SOD treatment preserved actin cytoskeleton organization and phagocytosis of Pseudomonas aeruginosa. 40 These findings suggest that decreased superoxide scavenging may directly contribute to the defective phagocytosis observed in these cells. The present study further supports these previous studies in observing that regulation of oxidant production is important in promoting macrophage function.…”
Section: Discussionmentioning
confidence: 95%
“…39 A more recent study found that hyperoxia reduces macrophage phagocytosis and that exogenous SOD treatment preserved actin cytoskeleton organization and phagocytosis of Pseudomonas aeruginosa. 40 These findings suggest that decreased superoxide scavenging may directly contribute to the defective phagocytosis observed in these cells. The present study further supports these previous studies in observing that regulation of oxidant production is important in promoting macrophage function.…”
Section: Discussionmentioning
confidence: 95%
“…Exposure to hyperoxia was performed in sealed humidified modular incubator chambers (BillupsRothenberg Inc., Del Mar, CA) containing 95% O 2 /5% CO 2 at 37°C, as described previously (Morrow et al, 2007). H 2 O 2 (30%) was purchased from VWR International (West Chester, PA).…”
Section: Cell Culture and Reagentsmentioning
confidence: 99%
“…The phagocytosis assay was performed as described with minor modifications (Baleeiro et al, 2003;Morrow et al, 2007). In brief, following each specific exposure, RAW 264.7 cells were treated with various concentrations of H 2 O 2 , ranging from 0 to 1000 µM for 1 h, and then incubated with PAO1 or fluorescein isothiocyanate (FITC)-labeled latex beads (Polysciences, Warrington, PA) at 100:1 [particles (beads or bacteria)/cell] at 37°C for 1 h. The macrophages were then washed with cold phosphate-buffered saline (PBS) containing 0.02% EDTA to remove the unbound particles and then treated with 0.04% trypan blue to quench the fluorescence attributable to any extracellular adherent particles.…”
Section: Phagocytosis Assaymentioning
confidence: 99%
See 2 more Smart Citations